2021
DOI: 10.3389/fmed.2021.745064
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Brain Positron Emission Tomography in Female 5XFAD Alzheimer Mice: Pathological Features and Sex-Specific Alterations

Abstract: Successful back-translating clinical biomarkers and molecular imaging methods of Alzheimer's disease (AD), including positron emission tomography (PET), are very valuable for the evaluation of new therapeutic strategies and increase the quality of preclinical studies. 18F-Fluorodeoxyglucose (FDG)–PET and 18F-Florbetaben–PET are clinically established biomarkers capturing two key pathological features of AD. However, the suitability of 18F-FDG– and amyloid–PET in the widely used 5XFAD mouse model of AD is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…The 5xFAD mice expressing Aβ plaques were found to be an excellent model to examine potential alterations in α4β2* nAChRs. The presence of Aβ plaques in these mice were confirmed in these mice using [ 124/125 I]IBETA and anti-Aβ IHC (Nguyen et al, 2022) and [ 18 F]flotaza (Kaur et al, 2021) and were consistent with the findings of [ 18 F]florbetaben (Boulter et al, 2021). In vitro binding of [ 125 I]IBETA and [ 124 I]IBETA in transgenic 5xFAD mouse model for Aβ plaques was high in the frontal cortex, anterior cingulate, thalamus, and hippocampus, which were regions of high Aβ accumulation, with very little binding in the cerebellum (ratio of brain regions to cerebellum was >5).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The 5xFAD mice expressing Aβ plaques were found to be an excellent model to examine potential alterations in α4β2* nAChRs. The presence of Aβ plaques in these mice were confirmed in these mice using [ 124/125 I]IBETA and anti-Aβ IHC (Nguyen et al, 2022) and [ 18 F]flotaza (Kaur et al, 2021) and were consistent with the findings of [ 18 F]florbetaben (Boulter et al, 2021). In vitro binding of [ 125 I]IBETA and [ 124 I]IBETA in transgenic 5xFAD mouse model for Aβ plaques was high in the frontal cortex, anterior cingulate, thalamus, and hippocampus, which were regions of high Aβ accumulation, with very little binding in the cerebellum (ratio of brain regions to cerebellum was >5).…”
Section: Discussionsupporting
confidence: 85%
“…At the age of 18 months, the mice develop extensive Aβ deposits and serve as good models of advanced human AD (Forner et al., 2021; Oblak et al., 2021). PET imaging studies in the 5xFAD transgenic mice have been carried out using various PET probes including Aβ plaque imaging [ 18 F]florbetaben (Boulter et al., 2021; Jullienne et al., 2022). Our recent findings using brain slices in vitro autoradiography and in vivo PET confirmed Aβ plaque accumulation in 5xFAD mice using the imaging agent [ 124/125 I]IBETA (Nguyen et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Bouter et al showed that early-age 5XFAD females exhibit lower brain metabolic uptake compared to controls. This global decrease likely overshadows any sex-dependent developmental differences in glucose metabolism [37]. Second, when comparing weighted distributions across genotype, we found a significant difference in edge weights (both positive and negative) between 12-month female WT and 5XFAD group networks (Figure 2F).…”
Section: Discussionmentioning
confidence: 84%
“…showed that early‐age 5XFAD females exhibit lower brain metabolic uptake compared to controls. This global decrease likely overshadows any sex‐dependent developmental differences in glucose metabolism 37 . Second, when comparing weighted distributions across genotype, we found a significant difference in edge weights (both positive and negative) between 12‐month female WT and 5XFAD group networks (Figure 2F).…”
Section: Discussionmentioning
confidence: 85%